Analisis Putusan Hakim terhadap Pelaku Tindak Pidana Pembunuhan Berencana Berdasarkan Putusan Nomor 668/Pid.B/2019/Pn.Jkt.Tim dan Putusan Nomor 1001/Pid.B/2021/Pn.Jkt.Tim - Soni Widianto (Jurnal Ilmiah Wahana Pendidikan, 2023)
In applying Article 340 of the Criminal Code to the case of premeditated murder based on Decision Number 668/PID.B/2019/PN.Jkt.Tim and Decision Number 1001/Pid.B/2021/PN.Jkt.Tim the Defendants were sentenced, then in accordance with the provisions of Article 222 paragraph (1) in conjunction with Article 197 paragraph (1) letter i of the Criminal Procedure Code, the Defendants are burdened to pay court costs and with due regard to the provisions of Article 340 Jo. Article 56 paragraph (2) of the Criminal Code. Meanwhile, in Decision Number 1001/Pid.B/2021/PN.Jkt.Tim the Defendant was charged with Article 340 of the Criminal Code where the judge was incorrect in the verdict, namely even though he had stated that the Defendant RIDHO IHWANSYAH BIN ROZALI was legally and convincingly proven guilty of committing the crime of "helping to commit premeditated murder" as charged in the PRIMAIR indictment of the Public Prosecutor and the Defendant ASEP SAEPUDIN alias ALEX BIN WAHYUDI based on Decision Number 1001/Pid. B/2021/PN.Jkt.Tim was found legally and convincingly guilty of committing the crime of premeditated murder as set out in the First Alternative Indictment. However, the Panel of Judges was unfair and did not maximize the punishment by only sentencing the defendant ASEP SAEPUDIN alias ALEX Bin WAHYUDI in the form of imprisonment for 15 (fifteen) years. Meanwhile, the Panel of Judges in Decision Number 668/PID.B/2019/PN.Jkt Tim only sentenced the Defendant RIDHO IHWANSYAH BIN ROZALI to imprisonment for only 8 (eight) years. The deliberate premeditated murder committed by the defendants should have been subject to a more severe criminal sanction, namely the death penalty.